Application Of Scaffolding Method in Improving Learning Outcomes of The Material on Resecting Parents At Mi Muhammadiyah Sidamulya - Hasanah, Uswatun; Ariana, Uti; Fitriana, Uun; Khasanah, Uswatun (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of the Scaffolding method in improving learning outcomes on respecting parents in class 1 of MI Muhammadiyah Sidamulya, Kemranjen, Banyumas, Central Java. The Scaffolding method is applied by providing gradual guidance according to the level of students' understanding, so that they can understand the material more deeply. This study uses a qualitative and quantitative approach with data collection techniques through observation, interviews, and learning outcome tests before and after the implementation of the Scaffolding method. The results showed that the Scaffolding method significantly improved students' understanding of the concept of respecting parents. Students became more active in the learning process, were able to internalize moral values, and showed more positive changes in attitudes in everyday life. The increase in the average value of learning outcomes after the implementation of this method showed the effectiveness of the learning strategy used. In addition to having an impact on academic results, the Scaffolding method also contributes to the formation of students' character. With gradual guidance and motivation from teachers, students become more confident in expressing opinions, interacting with peers, and implementing an attitude of respecting parents in their social lives. In conclusion, the Scaffolding method is an effective learning strategy to improve students' understanding and attitudes towards the material of respecting parents. Therefore, this method can be an alternative in learning Civic Education (PKN) in elementary schools to instill moral values ​​more deeply.